Volumetric neural correlates of visual working memory in obsessive-compulsive disorder : a voxel-based morphometry study - Yeo, Siok Peng (2018)
Neuropsychological studies have generally reported poor visual working memory (VWM) in patients with obsessive-compulsive disorder (OCD), though some proposed that the memory problem observed were secondary to impaired organisational strategies. These studies typically used tasks that also required other executive functions. Therefore, it is still unclear whether patients with OCD demonstrate deficits in VWM. Existing structural neuroimaging studies reported volumetric abnormalities within the cortico-striato-thalamo-cortical (CSTC) circuitry in OCD population. However, limited studies explored neural structures involved in VWM in OCD, specifically, the frontal-parietal network (FPN) and cerebellum region of interests (ROIs). This study evaluated VWM using the symbol span task and Sternberg VWM paradigm, and explored associations between volumetric correlates of the FPN and cerebellum with task performances and symptom severity in 21 patients and 17 matched controls. Compared to controls, OCD samples showed larger grey matter volume (GMV) in the right superior parietal cortex and smaller GMV in right precentral gyrus, right insula and left cerebellar lobule VIIIa, and had significantly poorer performance in the symbol span task and lower accuracy in the high-load condition of the Sternberg VWM task. GMV of the left cerebellum and vermis ROIs were significantly associated with VWM while the GMV of the bilateral cerebellum ROIs were significantly correlated with symptom severity scores. The current findings support that VWM performance could be affected in OCD patients under high demand conditions. In addition, brain regions involved in OCD pathophysiology appears not confined to CSTC circuit, and prompts further investigation of the cerebellar involvement in OCD.